Fractionation of coconut oil via supercritical fluid extraction for production of cocoa butter substitute - Abdul Halim, Halimatun Sa'adiah; Selamat, Jinap; Hussain, Norhayati (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Coconut oil (CNO) is a vegetable fat that can be applied as a cocoa butter substitute (CBS) due to its similar physical characteristics to cocoa butter. However, it must be fractionated or hydrogenated to be used as CBS. The aims of the present work was to fractionate CNO using supercritical fluid extraction (SFE), and determine the potential fraction which is suitable as CBS. CNO was fractionated by SFE at 48.3 MPa and 80°C into four different fractions, F1, F2, F3 and F4. Fraction 1 had the highest yield (48.9%) as compared to the other fractions. Fraction 4 had the lowest content of lauric acid, C12 (31.12%) and the highest amount of palmitic acid, C16 (16.43%); stearic acid, C18:0 (4.99%); and linoleic acid, C18:1 (17.44%). Fraction 4 also had the highest melting profile (25.24°C) and amount of solid fat content (state) closest to CB. Therefore, F4 was selected as a potential fraction for the application of CBS. This finding reveals that CNO can be fractionated by SFE and applied as CBS to help diversify the application of coconut products.